Implementação e monitoramento de um sistema de irrigação automatizado em IoT utilizando módulo ESP32 em plantio caseiro - Henriques, Luiz Felipe Araújo (Brasil, 2021)
This work consists of the development and implementation of an automated irrigation system based on the concepts of the Internet of Things. The proposed project was carried out using the communication protocol between MQTT machines and the ESP-WROOM-32 microcontroller module, for monitoring soil moisture and ambient temperature data collected by sensors in home planting, transmitted to the TagoIO IoT platform for the views of data received through dashboard graphics.